2023
DOI: 10.7717/peerj.14945
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to develop assessment tools for Group A Streptococcus surveillance studies

Abstract: Introduction Group A Streptococcus (GAS) causes pharyngitis (sore throat) and impetigo (skin sores) GAS pharyngitis triggers rheumatic fever (RF) with epidemiological evidence supporting that GAS impetigo may also trigger RF in Australian Aboriginal children. Understanding the concurrent burden of these superficial GAS infections is critical to RF prevention. This pilot study aimed to trial tools for concurrent surveillance of sore throats and skins sore for contemporary studies of RF pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A link between GAS pharyngitis and ARF is established, but throat carriage of GAS species is reportedly low in people in remote communities in Australia. In these settings, ARF is considered more likely to follow GAS impetigo although the pathogenesis is unclear [ 8 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A link between GAS pharyngitis and ARF is established, but throat carriage of GAS species is reportedly low in people in remote communities in Australia. In these settings, ARF is considered more likely to follow GAS impetigo although the pathogenesis is unclear [ 8 ].…”
mentioning
confidence: 99%
“…Research has demonstrated that treating human scabies reduces impetigo incidence in remote northern Australian communities [ 8 ]. There have been no studies of the effect of canine ectoparasite control on impetigo occurrence in people.…”
mentioning
confidence: 99%